A new species of Ferneiella from the Eocene French amber (Diptera: Scatopsidae) - Bramuzzo, S.; Coty, D.; Nel, A. (Zootaxa, 2017)
We describe the first fossil representative of the genus Ferneiella, F. gallica sp. nov., in the earliest Eocene Oise amber.